2014
DOI: 10.1016/j.vaccine.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of flagellin-L2 multimer vaccines protect against challenge with diverse papillomavirus genotypes

Abstract: Genetically modified bacterial flagellin (Fla), a Toll-like receptor-5 (TLR5) ligand, was evaluated as a fusion partner for human papillomavirus (HPV) L2-based immunogens in two animal challenge models; either cutaneous inoculation of rabbits with HPV ‘quasivirions’ containing cottontail rabbit papillomavirus (CRPV) genomes that induce warts, or intra-vaginal inoculation of mice with HPV ‘pseudovirions’ encapsidating a luciferase reporter plasmid and measurement of bioluminescence to determine infectivity. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 46 publications
(62 reference statements)
2
29
0
2
Order By: Relevance
“…These latter modifications are needed because of the sub-dominance of L2 within native HPV particles and the reduced immunity of L2 antigens presented separately [21,49,50]. Additional strategies to enhance the antigenicity of L2 have included L2 sequences fused to TLR5 activators [33], IgG1 Fc [51] and thioredoxin [52]. In some of these studies, the antigenicity of the L2 sequences remained low [53,54] and required potent and non-clinically relevant adjuvants to induce strong protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These latter modifications are needed because of the sub-dominance of L2 within native HPV particles and the reduced immunity of L2 antigens presented separately [21,49,50]. Additional strategies to enhance the antigenicity of L2 have included L2 sequences fused to TLR5 activators [33], IgG1 Fc [51] and thioredoxin [52]. In some of these studies, the antigenicity of the L2 sequences remained low [53,54] and required potent and non-clinically relevant adjuvants to induce strong protection.…”
Section: Discussionmentioning
confidence: 99%
“…Three days after challenge, the mice were again anesthetized and 20 μL of luciferin (7.8 mg/mL) was deposited in the vaginal vault. Luciferase signals were acquired for 10 min with a Xenogen IVIS 100 imager, and analysis was performed with Living Image 2.5 software [32,33]. …”
Section: Methodsmentioning
confidence: 99%
“…Однако N-конец белка L2 содержит консервативные эпитопы, к которым возможно образование нейтрализующих антител [14,20,33]. В литера-туре описаны успешные попытки повышения иммуногенности N-конца молекулы L2 путем слияния в одном белке N-концов белка L2 сразу нескольких штаммов [20,21,22,24].…”
Section: Discussionunclassified
“…Та-ким образом, при создании вакцины на основе L2 необходимо повысить его иммуногенность. Одним из методов решения этой задачи являет-ся конкатомеризация N-концов L2 различных штаммов ВПЧ [20,21,22,24]. Повышение имму-ногенности в этом случае объясняется наличием в одном белке множества одинаковых эпитопов, что вызывает интернализацию B-клеточных рецепторов на поверхности B-клетки и индук-цию ее пролиферации [1].…”
Section: Introductionunclassified
“…As an alternative to vaccines based on L1 VLPs, we and others have focused on developing broadly protective cost-effective next-generation HPV vaccines targeting highly conserved epitopes in the HPV minor capsid protein, L2 [9, 16, 17, 25-29]. Our group has developed candidate next-generation HPV vaccines based on bacteriophage VLPs displaying conserved L2 epitopes from HPVs and has shown that these vaccines provide broad protection from infection by diverse HPV types [9, 15-18].…”
Section: Discussionmentioning
confidence: 99%